Research on the Path of Digital Rural Construction Boosting Rural Revitalization - Lan, Zhu (Transactions on Economics, Business and Management Research, 2024)
This article delves into the significant role of digital rural construction in the path of rural revitalization. Through analyzing the practical applications of digital rural construction, the article elaborates on the specific applications of intelligent agricultural equipment, precision agriculture, agricultural big data, and other technologies in improving agricultural production efficiency, expanding agricultural product markets, and strengthening rural governance and social services. This study further proposes strategies and suggestions such as strengthening top-level design, increasing capital investment, cultivating and introducing talents, and innovating institutional mechanisms to promote the comprehensive advancement of digital rural construction and inject new vitality into rural revitalization.